Impacts of nano-clay particles and heat-treating on out-of-phase thermo-mechanical fatigue characteristics in piston aluminum-silicon alloys - H. Bahmanabadi; M. Azadi; A. Dadashi; J. Torkian; M.S.A. Parast; G. Winter; F. Grun (Fracture and Structural Integrity)
In this article, the effect of nano-clay particles and heat-treating on thermo-mechanical fatigue (TMF) behaviors and failures of piston aluminum-silicon (AlSi) alloys was investigated. For this purpose, thermo-mechanical fatigue tests were conducted under out-of-phase (OP) loading conditions. Two loading conditions were checked based on different maximum temperatures (250, 300 and 350 C) and various thermo-mechanical loading factors (100, 125 and 150%). The minimum temperature was constant in all tests at 50 C under a heating/cooling rate of 10 C/s and a dwell time of 5 s. Results showed that the nano-composites had a longer fatigue lifetime, at least 2 times higher, compared to the Al alloy, when the maximum temperature was 250 C and the thermo-mechanical loading factor was 100%. However, no effective change was seen for the stress value and the plastic strain. At higher maximum temperatures, the change in the material behavior was lower. The fracture analysis by scanning electron microscopy (SEM) demonstrated that both materials had a brittle behavior due to cleavage and quasi-cleavage marks. The damage mechanism was also due to the Si-rich phase and intermetallics, respectively for the crack propagation and the micro-crack initiation